Antarctic beaked whale echolocation signals near South Scotia Ridge - Trickey, Jennifer S. (2015)
Several species of beaked whales inhabit the Southern Ocean, but information on their abundance, distribution, and seasonality is scarce. However, beaked whales are the only cetaceans known to use frequency modulated (FM) upsweep pulses to echolocate, and these signals appear to be species-specific in their spectral and temporal properties. Accordingly, passive acoustic monitoring has proven useful to investigate the behavioral ecology of these elusive species. Acoustic recordings were collected in Antarctic waters with both a towed hydrophone array as well as a bottom-moored High-frequency Acoustic Recording Package (HARP) deployed near Elephant Island that recorded between March and July 2014. The acoustic data revealed several beaked whale signal types of unknown origin. Of the five species of beaked whales known to occur in the survey area, an acoustic description has only been made for the FM pulses produced by Cuvier?s beaked whales (Ziphius cavirostris). Signal characterization using custom MATLAB-based routines determined that three unidentified FM pulse types are distinctly different from the signal of Cuvier?s beaked whales, and are also unlikely to belong to Arnoux?s beaked whales (Berardius arnuxii). Southern bottlenose whales (Hyperoodon planifrons) likely produce the most dominant beaked whale signal type (BW29) in the towed array and HARP data. The sources of the two less commonly detected echolocation signals, BW37 and BW55, are possibly Gray?s beaked whales (Mesoplodon grayi) and strap-toothed whales (M. layardii). Acoustic encounters over several months indicated differences among the various species in diel and seasonal use of the area near the recorder. Ongoing passive acoustic monitoring in the Southern Ocean will allow us to explore long-term relative abundance and distribution, as well as consistent seasonal and diel patterns, and will provide insight into the ecological role of beaked whales in an ecosystem that is undergoing rapid environmental transitions as a result of climate change.